2013
DOI: 10.1159/000342511
|View full text |Cite
|
Sign up to set email alerts
|

Human Congenital Perilipin Deficiency and Insulin Resistance

Abstract: Lipid droplets (LDs) can form in all eukaryotic cells, but white adipocytes are uniquely adapted to store energy as neutral lipid within a large unilocular LD. Non-esterified fatty acids can then be released from the LD store by lipases for use in oxidative tissues. Perilipin was the first mammalian LD protein to be identified in adipocytes where it plays a key role in co-ordinating access of lipases to the core triacylglycerol. We recently identified the first human loss-of-function mutations in PLIN1 in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This delicate balance between lipid storage and release may underlie the often contradictory data surrounding association of lipid storage genes expression with metabolic health. On one hand, human studies have shown that increased expression of lipogenic genes CIDE and perilipin in adipose were correlated with lower BMI and higher insulin sensitivity, and humans with perilipin deficiency have severe insulin resistance [54]. On the contrary, both CIDEC and perilipin1 knockout mice were protected against obesity and insulin resistance [55], underscoring the importance of human models in understanding lipid physiology.…”
Section: Discussionmentioning
confidence: 99%
“…This delicate balance between lipid storage and release may underlie the often contradictory data surrounding association of lipid storage genes expression with metabolic health. On one hand, human studies have shown that increased expression of lipogenic genes CIDE and perilipin in adipose were correlated with lower BMI and higher insulin sensitivity, and humans with perilipin deficiency have severe insulin resistance [54]. On the contrary, both CIDEC and perilipin1 knockout mice were protected against obesity and insulin resistance [55], underscoring the importance of human models in understanding lipid physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations causing autosomal dominant FPLD lead to a relative diminution of subcutaneous adipose tissue on the limbs, though this may sometimes be subtle, with severe dyslipidemia and often early onset hypertension [48]. A handful of rarer mutations have also been described, including defects in two different lipid droplet proteins, perilipin [49] and CIDEC [50], which play distinct roles in the mobilization of triglyceride stores from the single large lipid droplet in fat cells. Deficiency of CIDEC in a single patient has been shown to give rise to a unique multilocular appearance of residual white adipose tissue, quite unlike the usual single large lipid droplet normally seen [50].…”
Section: Lipodystrophic Insulin Resistancementioning
confidence: 99%
“…PLIN2-KO mice are also protected against diet induced obesity, fatty liver and inflammation presumably via increased browning and decreased food intake (McManaman JL, 2013). On the other hand, PLIN1 loss of function mutation causes increased basal lipolysis, lipodystrophy and insulin resistance in humans (Kozusko K, 2013) which is explainable as the balance between lipolysis and energy expenditure is disturbed which is important to maintain insulin sensitivity. Thus, targeting PLIN1 and energy expenditure is beneficial in obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%